Clinical and Infection Prevention Applications of Severe Acute Respiratory Syndrome Coronavirus 2 Genotyping: An Infectious Diseases Society of America/American Society for Microbiology Consensus Review Document. (3rd November 2021) - Greninger, Alexander L; Dien Bard, Jennifer; Colgrove, Robert C; Graf, Erin H; Hanson, Kimberly E; Hayden, Mary K; Humphries, Romney M; Lowe, Christopher F; Miller, Melissa B; Pillai, Dylan R; Rhoads, Daniel D; Yao, Joseph D; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged into a world of maturing pathogen genomics, with >2 million genomes sequenced at this writing. The rise of more transmissible variants of concern that affect vaccine and therapeutic effectiveness has led to widespread interest in SARS-CoV-2 evolution. Clinicians are also eager to take advantage of the information provided by SARS-CoV-2 genotyping beyond surveillance purposes. Here, we review the potential role of SARS-CoV-2 genotyping in clinical care. The review covers clinical use cases for SARS-CoV-2 genotyping, methods of SARS-CoV-2 genotyping, assay validation and regulatory requirements, clinical reporting for laboratories, and emerging issues in clinical SARS-CoV-2 sequencing. While clinical uses of SARS-CoV-2 genotyping are currently limited, rapid technological change along with a growing ability to interpret variants in real time foretell a growing role for SARS-CoV-2 genotyping in clinical care as continuing data emerge on vaccine and therapeutic efficacy. Abstract : This article reviews the potential role of SARS-CoV-2 genotyping in clinical care. Rapid technological change along with a growing ability to interpret variants in real-time foretell a growing role for SARS-CoV-2 genotyping in clinical care.